2021
DOI: 10.3389/fpsyg.2021.610670
|View full text |Cite
|
Sign up to set email alerts
|

Stressful Experiences in University Predict Non-suicidal Self-Injury Through Emotional Reactivity

Abstract: Theoretical perspectives on non-suicidal self-injury (NSSI; direct and deliberate self-injury without lethal intent such as self-cutting or hitting) have long underscored the affective regulating properties of NSSI. Less attention has been given to the processes through which individuals choose to engage in NSSI, specifically, to regulate their distress. In the present study, we tested one theoretical model in which recent stressful experiences facilitates NSSI through emotional reactivity. Further, we tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 89 publications
0
16
0
Order By: Relevance
“…Accordingly, students may use emotion-regulating behaviors like self-injury to cope with college-related stressful experiences (Hamza, Goldstein, Heath, & Ewing, 2021). Researchers have observed that 25–63% of those with adolescent-onset NSSI continue to self-injure (Glenn & Klonsky, 2011; Hamza & Willoughby, 2014), and 7% begin repetitive NSSI during the college years (Kiekens et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, students may use emotion-regulating behaviors like self-injury to cope with college-related stressful experiences (Hamza, Goldstein, Heath, & Ewing, 2021). Researchers have observed that 25–63% of those with adolescent-onset NSSI continue to self-injure (Glenn & Klonsky, 2011; Hamza & Willoughby, 2014), and 7% begin repetitive NSSI during the college years (Kiekens et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they frequently verbalise feelings of hatred towards the people around them or even towards themselves, an indication of self-esteem problems. Some even involved episodes of self-harm [41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…The ERS total had a significant positive correlation with less appropriate coping skills (e.g., passive depressive reaction patterns and avoidance) and a negative correlation with adequate coping skills (e.g., active problem solving) (29). A study in Canada surveyed 1,125 young adults in their first year of study at a large academic institution and found an indirect effect of recent stressful experiences on NSSI engagement through ER (30). According to Nock et al (23) examining the longitudinal course of ER and its expected relationship to psychopathology and self-injurious thoughts and behaviors is an interesting and likely fruitful area for research.…”
Section: Introductionmentioning
confidence: 99%